High-density lipoprotein cholesterol, apolipoprotein E and atherogenic index of plasma are associated with risk of chronic kidney disease - Jasmina Smajić; Sabaheta Hasić; Senija Rašić (Medicinski glasnik, 2018)
Aim: To investigate the association of parameters of lipid profile and estimated glomerular filtration rate (eGFR) <60 ml/min/1.73 m 2 calculated by the Modification of Diet in Renal Disease (MDRD) in non-dialysis kidney patients. Methods: The observational, case-control study enrolled patients (n=117) recruited from the Nephrological Counselling Centre of the University Clinical Centre Sarajevo and divided into two groups: group 1 eGFR (15-59 mL/min/1.73 m 2), and group 2 (control) eGFR ? 60 mL/min/1.73 m 2. Concentration of lipids, lipoproteins and apolipoproteins was measured, and atherogenic index of plasma (AIP; log(TG/HDLc)) was calculated. Results: High density lipoprotein cholesterol (HDLc) and apolipoprotein E (APOE) concentrations in serum were reduced [(1.02 (0.94-1.29) vs 1.15 (1.1-1.4) mmol/L; p=0.009 and 0.035 (0.026-0.04) vs 0.041 (0.034-0.05) g/L; p=0.002, respectively)], while AIP was higher in group 1 than in group 2 (0.19±0.03 vs 0.09±0.04; p=0.013). Values less than 1.09 mmol/L and 0.038 g/L for HDLc and APOE, or higher than 0.165 for AIP (p<0.05) were associated with the eGFR below 60 ml/min/1.73 m 2. The age [OR = 1.1; 95% CI (1.05-1.17)] and AIP [OR = 8.7; 95% CI (1.18-65.0)] were independent positive predictors, while APOE was a negative predictor of eGFR reduction rate (OR=0.01; 95% CI (0.001-0.033; p<0.001). Conclusion: Changes in parameters such as HDLc, APOE and AIP are associated with CKD. The study results imply the need of the AIP calculation as routine laboratory work due to its role along with the age and APOE in the prediction of renal function decline.
Keywords: kidney failure; estimated glomerular filtration rate; lipid profile